ANALISIS LOMPAT VERTIKAL TIPE SQUAT DENGAN MODEL SISTEM BENDA JAMAK - Susilo, D D; Mahyuddin, A. I; Nurprasetio, I. P (Mesin, 2009)
Vertical jump is a good indicator for success in sports that need strength and speed of lower extremity such as basketball, volleyball, and soccer. The skeletal model of human body is treated as a two dimensional multibody system to analyze vertical jump. The squat jump of a particular subject could be simulated on the multi-body system model. The simulation results in the maximum jump height in close agreement with the height obtained via the flight time method analysis. Hence, the simple multibody model is deemed adequate for squat jump analysis. Furthermore, the results of this research could be used as a basis for further modeling and analysis improvement. Advanced model should take into account the effects of the muscles. Accurate measurement could be achieved by employing better sensors and data acquisition system. Future results of investigation in the area of dynamics of human movement could serve the sport world and medical rehabilitation program.